Bacterial biofilms and capsular contracture in patients with breast implants. Issue 6 (6th March 2013) - Rieger, U. M.; Mesina, J.; Kalbermatten, D. F.; Haug, M.; Frey, H. P.; Pico, R.; Frei, R.; Pierer, G.; Lüscher, N. J.; Trampuz, A.
Abstract : Background: It has been hypothesized that bacterial biofilms on breast implants may cause chronic inflammation leading to capsular contracture. The association between bacterial biofilms of removed implants and capsular contracture was investigated. Methods: Breast implants explanted between 2006 and 2010 at five participating centres for plastic and reconstructive surgery were investigated by sonication. Bacterial cultures derived from sonication were correlated with patient, surgical and implant characteristics, and the degree of capsular contracture. Results: The study included 121 breast implants from 84 patients, of which 119 originated from women and two from men undergoing gender reassignment. Some 50 breast prostheses were implanted for reconstruction, 48 for aesthetic reasons and 23 implants were used as temporary expander devices. The median indwelling time was 4·0 (range 0·1–32) years for permanent implants and 3 (range 1–6) months for temporary devices. Excluding nine implants with clinical signs of infection, sonication cultures were positive in 40 (45 per cent) of 89 permanent implants and in 12 (52 per cent) of 23 temporary devices. Analysis of permanent implants showed that a positive bacterial culture after sonication correlated with the degree of capsular contracture: Baker I, two of 11 implants; Baker II, two of ten; Baker III, nine of 23; and Baker IV, 27 of 45 ( P < 0·001). The most frequent organisms were Propionibacterium acnes (25 implants) and coagulase‐negative staphylococci (21). Conclusion: Sonication cultures correlated with the degree of capsular contracture, indicating the potential causative role of bacterial biofilms in the pathogenesis of capsular contracture. Registration number: NCT01138891 (http://www.clinicaltrials.gov). Abstract : Subclinical infection is of major importance